2001
DOI: 10.1106/3c68-twxp-qmea-6ufk
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Metallocene Propylene Polymers for Cast Film Applications

Abstract: The entry of metallocene-based products into polypropylene (pp) cast film is at a stage where their potential in various markets is now being assessed. This study reviews the structural features of some metallocene polymers and reports on resulting potential benefits in cast film applications through their use—and also with their use—in blends with Ziegler-Natta based PP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Advances in catalyst technology make it possible to synthesize polypropylenes and propylene copolymers that differ substantially in molecular weight and molecular weight distribution, in stereo defect type and distribution, and in comonomer distribution. It has been suggested that this unprecedented control of the molecular structure can lead to a set of differentiated properties of oriented film 1, 14, 15. In the present study, three isotactic polypropylene resins that differed in the chain architecture were biaxially oriented at various temperatures close to the peak melting temperature.…”
Section: Introductionmentioning
confidence: 75%
“…Advances in catalyst technology make it possible to synthesize polypropylenes and propylene copolymers that differ substantially in molecular weight and molecular weight distribution, in stereo defect type and distribution, and in comonomer distribution. It has been suggested that this unprecedented control of the molecular structure can lead to a set of differentiated properties of oriented film 1, 14, 15. In the present study, three isotactic polypropylene resins that differed in the chain architecture were biaxially oriented at various temperatures close to the peak melting temperature.…”
Section: Introductionmentioning
confidence: 75%